Resource use decrease after implementation of care bundles for treatment of postpartum hemorrhage. (12th December 2022) - Escobar, María Fernanda; Valencia, Paola; Jaimes, Lina María; Hincapié, Lina Constanza; Pulgarín, Edwin Estiven; Nasner, Daniela; Carvajal, Javier; Echavarría, María Paula; Burke, Thomas; Prada, Sergio
Abstract: Objective: To evaluate whether the implementation of care bundles has an impact on resource utilization in the care of patients with postpartum hemorrhage (PPH). Methods: Retrospective, cross-sectional, observational study of 404 patients with stage II or greater PPH. Periods 2011–2014 and 2015–2017, before and after the introduction of care bundles, were compared. Billing reports were analyzed, and all services provided to treat these events were extracted. Use of resources within the two periods was computed. Results: The amount billed per episode decreased 18.66% from the first to the second period. Most PPH cases used fewer resources after introduction of care bundles. The greatest reduction was in the use of medications, with a decrease of charges by 56.3%. Diagnostic procedure charges decreased by 47.6% and consultation charges decreased by (37.7%). Conclusions: The use of PPH care bundles may be associated with lower resource use and fewer interventions.